Microscopic regulation of plant morphological pores on mechanical properties of porous mullite materials. Issue 2 (25th December 2020) - Hu, Jiaojiao; Li, Shujing; Li, Yuanbing; Li, Xuesong; Xiang, Ruofei; Qiao, Zhe
Abstract: Generally, a multilayer structure is present inside a walnut shell, and the residual structure of the walnut shell is retained after impregnation and firing. When the walnut shell is used as a pore‐forming agent, this structure helps in improving the mechanical and thermal insulation properties of the lightweight porous materials. In this study, porous mullite materials (PMMs) with plant morphological structure pores were prepared using a‐Al2 O3 and silica powder as the raw materials with addition of sol‐impregnated walnut shell powder (WSP). The influence of sol type and firing temperature on the pore structure of the PMMs was analyzed, which affected the compressive strength and thermal conductivity. The plant morphological porous structure was observed in the samples after sol impregnation. After firing at different temperatures, the porous structure gradually contracted and supported the pores, improving the mechanical properties, while the complex porous structure increased the heat conduction path, thereby improving the insulation performance. Using WSP impregnated with silica‐sol and zirconia‐sol as pore‐forming agents, PMMs with higher compressive strength and relatively low thermal conductivity (TC) were prepared.